Taxonomic Approach for Species Diversity of Yeasts and Yeasts-like Fungi through D1/D2 Region of Large Subunit Ribosomal DNA Sequences - Sumerta, I Nyoman; Kanti, Atit (Biosaintifika: Journal of Biology & Biology Education, 2018)
The identification of yeasts or yeasts-like fungi and verify their diversity are principal aspect for bioindustry and ecosystem sustainability. Taxonomic approach provides identification tool to ensure the taxonomic position of yeasts and yeasts-like fungi which definitely set to utilization concerns. The aim of this study is to understanding the taxonomic position of yeasts and yeasts-like fungi from the distinctive of its sequences relationship. Yeasts and yeasts-like fungi strains were isolated through various culture dependent methods from natural resources samples of Karimun Besar Island, Province of Riau Islands, Indonesia. The identification process was performed through amplifying the accurate DNA-based in D1/D2 region of large subunit (26S) ribosomal DNA. As the result, a total of 85 isolates of yeasts and yeasts-like fungi were obtained with 16 closest related taxa through phylogenetic tree construction. Ascomycetous was the predominating group representing 91% of the total isolates sequences followed by Basidiomycetous (8%) and Zygomycetous (1%). The black yeasts (yeasts-like) known as Aureobasidium melanogenum was predominant species with represent to 54% of total isolates and present in particular habitat. Taxonomically, there are six isolates are represent to be novel taxa candidates which pretend to enhance genetic resources of yeasts and yeasts-like fungi especially from Indonesia. In addition, this information provides specific technique to reach specific yeasts or yeasts-like fungi species in nature by managing the sample collection and culture methods.